The Influence of Online Customer Review, Customer Rating, and Viral Marketing on Purchase Decisions in Generation Z at Tokopedia - Aida Faradilla Kamal; Nobelson Nobelson; Yudi Nur Supriadi (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2023)
Tokopedia is the most visited e-commerce platform in Indonesia. But now there is a problem because Tokopedia is still below its competitors in purchasing decisions for generation Z. So the problem formulation in this study is whether customer reviews, customer ratings, and viral marketing influence purchasing decisions. This study has the objective of knowing, proving, and analyzing the influence of customer reviews, customer ratings, and viral marketing on purchasing decisions. The population in this study is generation Z consumers who have made purchases at Tokopedia in Jakarta. The sample used was 100 respondents, with quantitative data types and non-probability sampling methods (purposive sampling). The analysis technique uses Partial Least Square (PLS) with SmartPLS 3.0 software. The results of this study indicate that the variables customer review, customer rating, and viral marketing have a positive and significant impact on purchasing decisions. This study obtained the result that the customer review variable had the highest influence on the t-statistic test, which was 49.2%. Keywords:customer reviews, customer ratings, viral marketing,purchase decision, e-commerce